Christianity and the transformation of physical education and sport in China - Zhang, Huijie, author.
1 online resource (ix, 126 pages)
Keywords: "Despite the popularity of sport in contemporary China, the practice of physical education is not indigenous to its culture. Strenuous physical activity was traditionally linked to low class and status in the pre-modern Chinese society. The concept of modern PE was introduced to China by Western Christian missionaries and directors of the Young Men'; s Christian Association (YMCA). It then grew from a tool for Christian evangelism to a strategic instrument in Chinese nation-building.This book examines the transformation of Chinese attitudes toward PE and sport, drawing on the concepts of cultural imperialism and nationalism to understand how an imported Western activity became a key aspect of modernization for the Chinese state. More specifically, it looks at the relationship between Christianity and the rise of Chinese nationalism between 1840 and 1937. Combining historical insight with original research, this book sheds new light on the evolution of PE and sport in modern China.It is fascinating reading for all those with an interest in sports history, Chinese culture and society, Christianity, physical education or the sociology of sport. "--Provided by publisher.